THE EFFECT OF DRAGON FRUIT SKIN FLOUR FERMENTED WITH Saccharomyces cerevisiae IN RATIONS ON THE PERFORMANCE OF BROILER AGED 5 WEEKS - B., Syamsi; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This study aims to know the effect of dragon fruit skin flour fermented with Saccharomyces cerevisiae in ration on the performance of broiler aged 5 weeks ( bio-supplement ). The research was conducted at Research Station of Faculty of Animal Science, The University of Udayana, Jimbaran, Badung, Bali, for 5 weeks. Using Completely Randomized Design (CRD) with 3 treatments i.e. RKBN0 = Ration with no dragon fruit skin, RKBN1 = Ration with 5% fermented dragon fruit skin flour, RKBN2 = Ration with 7% fermented dragon fruit skin flour; with 6 replications where each replication consisted of 5 broilers.  Total used were 90 broilers with the initial body weights were 153,33± 3,01 g/ekor.  The variables observed were initial body weight (g), ration consumption (g), body weight gain (g), final body weight (g) and FCR ( Feed Conversion Ratio ). The data was analysed for its variance (Anova). The results showed that the giving of dragon fruit skin flour fermented with Saccharomyces cerevisiae in rations with 0%, 5% and 7% levels resulted in total ration consumption, body weight gain and final body weight of 2172 -2329 g, 1251 - 1323 g, respectively 1404 - 1476 g which statistically is not significant (P> 0.05). Whereas for Feed Convertion Ratio / FCR, giving of dragon fruit with level 7% (RKBN2) able to yield the lowest FCR value (1,65) that is 11,76% lower and significantly different (P<0,05) compared with treatment without flour dragon fruit skin (RKBN0). Based on the result of the research, it can be concluded that the giving of fruits dragon fruit powder fermented by Saccharomyces cerevisiae as much as 7% in ration can decrease FCR broiler 11,76%, but not influence ration consumption, body weight gain and broiler end body weight 1 - 5 weeks. Keywords: Broiler, performance, 5 weeks, dragon fruit skin flour, Saccharomyces cerevisiae